Local diagnostic reference levels for routine chest X-ray examinations at a public sector hospital in central South Africa - Maurice Junda; Henra Muller; Hesta Friedrich-Nel (AOSIS, 2021)
Background: Dose optimisation is a radiation protection guideline recommended by the International Commission on Radiological Protection (ICRP) for adherence to the 'as low as reasonably achievable' (ALARA) principle. Diagnostic reference levels (DRLs) are used to optimise patients' radiation protection for diagnostic and interventional procedures and are particularly useful for frequently performed examinations such as chest X-rays. Aim: To establish the local diagnostic reference levels (LDRLs) for routine chest X-rays. Setting: Public sector hospital, Northern Cape province, South Africa. Methods: Sixty patients referred for chest X-rays fulfilling the inclusion criteria participated in this study. Patients were ≥ 18 years of age and weighed between 60 kg and 80 kg. Consent for participation was obtained. The entrance skin air kerma (ESAK) was measured by using the indirect method recommended by the International Atomic Energy Agency (IAEA). Statistical software (SAS version 9.2) was used to determine the LDRLs for chest X-rays in three different rooms. In two rooms, computed radiography (CR) was used and the other one was a digital radiography (DR) unit. The LDRL values at the research site were compared with various published international values. Results: LDRLs for chest X-rays were established. The CR LDRL value for the posteroanterior (PA) chest projection was higher than the DR (flat panel detector [FPD]) LDRL value. The LDRLs of the PA chest projections were 0.3 mGy for CR and 0.2 mGy for DR. The lateral (LAT) chest projection LDRL value was 0.8 mGy for both CR and DR (FPD) projections. The resultant LDRL between rooms at the research site was 0.3 mGy for PA 0.3 mGy and 0.8 mGy for LAT chest projections. Conclusion: The LDRLs for chest X-rays established at this research site were lower than internationally reported DRLs. We recommend that LDRLs for routine chest X-rays should be repeated every 3 years, according to the ICRP. Contribution: Currently, no established or published DRL values prescribed by the Directorate of Radiation Control (DRC) are available in South Africa. The LDRLs established for routine chest X-ray examinations at this research site can serve as a guideline for the establishment of DRL values for other anatomical regions at the research site and other radiology departments in the country.